Clinico-etiological profile of neonates admitted with jaundice in a tertiary care NICU of Central India - Kalraiya, Ashish; Gyanani, Pankaj; Dubey, Shiv Ram Krishna; Beohar, Vijaya; Verma, Pramila (International Journal of Contemporary Pediatrics, 2018)
Background: Hyperbilirubinemia is a common problem and, in most cases, a benign problem in neonates. Jaundice is observed during the 1st week of life in approximately 60% of term infants and 80% of preterm infants. Methods: In present study, total 187 newborns were enrolled prospectively over one and half year of study period from November 2015 to April 2017. Detailed patient information was taken at the time of admission in NICU. In this study all the newborns with age less than 28 days were included who had clinical jaundice, ascertained by Kramer’s criteria and confirmed by biochemical methods. The investigations done were Serum bilirubin (total, direct and indirect) complete blood picture, reticulocyte count, G6-PD estimation (qualitative), Coombs' test, peripheral smear examination, blood group (ABO,Rh) of the mother and baby, CBC,CRP, thyroid function test. Results: Total 187 newborns were enrolled for study. Maximum number of the babies have a pathological jaundice 108 (57.7%) whereas 79 (42.24%) were found to have exaggerated physiological jaundice. The commonest causes of pathological jaundice were found to be septicemia 63 (33.68%) followed by ABO incompatibility 25 (13.36%). Most of the babies had onset of jaundice between 24-72 hours (86.6%). Conclusions: Health care providers working with neonates play a key role in identifying and assessing neonates at risk for pathologic jaundice. Parents counseling is required for bringing their babies early to healthcare centre preventing acute bilirubin encephalopathy and subsequent kernicterus.